Sobre la negació en català - Morant Marco, Ricard; Pérez Saldanya, Manuel (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: The authors propose the study of negative activators and terms of negative polarity in Catlana starting from the following four structures: logical, concordant, linear and pragmatic.